Reduksionisme Vs Holisme dalam Membentuk Opini Publik tentang Kebijakan Hak Senjata: Analisis Komparatif Partai-Partai Politik Utama Amerika: Reduksionisme Vs Holisme dalam Membentuk Opini Publik tentang Kebijakan Hak Senjata: Analisis Komparatif Partai-Partai Politik Utama Amerika - Dahlan, A. Fahmi (Jurnal Filsafat Indonesia, 2025)
The debate over gun ownership rights in the United States remains one of the most polarized political issues, reflecting fundamentally different worldviews between Republicans and Democrats. These divergent perspectives can be traced to philosophical orientations that shape both policy design and public discourse. This study employs a mixed-methods approach, combining analysis of policy documents, media coverage, and political messaging, to investigate how reductionist and holistic frameworks influence gun rights debates over the past two decades. Drawing on Risjord’s conceptualization, reductionism is understood as an approach that isolates specific factors, prioritizes individual rights, and advances narrowly targeted interventions. Within the American political context, Republicans often embrace this framework, emphasizing the Second Amendment as the central guarantee of personal liberty and self-defense. In contrast, holism emphasizes the interconnectedness of social systems and advocates comprehensive solutions that address root causes. Democrats frequently adopt this orientation, framing gun violence as a public health crisis that requires systemic reforms addressing poverty, inequality, and mental health. The findings reveal that reductionist discourse tends to construct gun rights as a constitutional and individual security issue, while holistic discourse frames gun violence as a collective challenge embedded in broader social structures. This contrast highlights how deeply ingrained philosophical orientations shape political communication and public opinion. Importantly, the study identifies areas of overlap that may inform more effective, unified approaches to firearm policy in the United States.